Performance analysis of solar-powered integrated desalination and air conditioning system. Issue 3 (14th September 2022) - Saxena, Akash; Tangellapalli, Srinivas
ABSTRACT: During the operation of the vapor compression refrigeration (VCR) cycle, heat is absorbed in the evaporator and rejected from the condenser to the environment. The heat rejected by the condenser is often wasted, and it raises the ambient air temperature, resulting in thermal pollution. Apart from that, freshwater scarcity is a severe concern in many areas. An integrated system of humidification-dehumidification (HDH) desalination and air conditioning using waste heat from the VCR system is proposed to address these difficulties. The system provides freshwater, cooled air, and hot water while preventing thermal pollution. Although the combination of desalination and cooling systems has piqued the attention of a few researchers, the duct architecture used in this work is a first. The study determines an appropriate humidifier spray water temperature based on human comfort conditions. It investigates the effects of ambient temperature and relative humidity, saline water temperature, and humidifier efficiency on output and performance metrics. The experimental studies are used to validate the thermodynamic model established in this paper. From one cubic meter of air, 31.50 kJ of heat and 40.53 mL of freshwater are extracted using 0.66 kW of power. The cooling performance (CP), gained output ratio (GOR), coefficient of energy performance (COEP), and exergy efficiency for the given operating parameters are 1.34, 4.29, 1.72, and 13.99%, respectively. The cost of freshwater production is $ 0.010076 per liter.